Using Mobile-Based Social Networks by Iranian Libraries: The Case of Telegram Messenger - Asnafi, Amir Reza; Moradi, Shima; Dokhtesmati, Mohadeseh; Naeini, Maryam Pakdaman (Library philosophy and practice, 2017)
The purpose the present research was to examine the use of Telegram Messenger as a mobile-based social network in Iranian academic libraries. Data were collected from March 2016 to May 2016. Telegram channels of different libraries were identified through the websites of the National Library of Iran and individual academic libraries. quantitative analyses were carried out on the data. Researchers joined these channels to examine their content. Descriptive statistics was used for data analysis. The results showed that files, news and information, book introductions, and literary quotes were the main materials shared on these channels. Most posts contained images. The central library of Sharif University of Technology used hashtags for most of its posts. Moreover, libraries with more activities and programs shared more book introductions and reports. University libraries shared more technical materials such as research methodology, essay writing, and database information. However, posts from other libraries were mostly nontechnical. Mobile-based services have had a significant influence on academic libraries around the world. The findings have enabled us to better understand impact of using mobile-based services in Iranian libraries.